Time-on-pitch or full-game GPS analysis procedures for elite field hockey? - White, A. D.; MacFarlane, N. (International Journal of Sports Physiology and Performance, 2013)
Purpose: The current study assessed the impact of full-game (FG) and time-on-pitch (TOP) procedures for global-positioning-system (GPS) analysis on the commonly used markers of physical performance in elite field hockey. Methods: Sixteen international male field hockey players, age 19-30, were studied (yielding 73 player analyses over 8 games). Physical activity was recorded using a 5-Hz GPS. Results: Distance covered, player load, maximum velocity, high-acceleration efforts, and distance covered at specified speed zones were all agreeable for both analysis procedures (P > .05). However, percentage time spent in 0-6 km/h was higher for FG (ES: -21% to -16%; P < .001), whereas the percentage time in all other speed zones (1.67-3.06 m/s, 3.06-4.17 m/s, 4.17-5.28 m/s, and > 6.39 m/s) and relative distance (m/min) were higher for TOP (ES: 8-10%, 2-7%, 2-3%, 1-1%, 0-1%, respectively; P < .001). Conclusions: These data demonstrate that GPS analysis procedures should be appropriate for the nature of the sport being studied. In field hockey, TOP and FG analysis procedures are comparable for distance-related variables but significantly different for time-dependent factors. Using inappropriate analysis procedures can alter the perceived physiological demand of elite field hockey because of "rolling" substitutions. Inaccurate perception of physiological demand could negatively influence training prescription (for both intensity and volume).